FUNGAL INFECTION: A RARE CAUSE OF GASTRIC PERFORATION - Habib, Rohan; Afzal, Muhammad Waqas; Ahmed, Fahad (Journal of Ayub Medical College Abbottabad, 2020)
Gastric perforation is among one of the common indications for a laparotomy. It can occur as a result of an erosive ulcer, long term usage of NSAIDs and malignancy among other causes. Here we report a case of a 70-year-old man with an invasive fungal infection as a cause of his gastric perforation based on histopathological evidence. Although very rare it should be kept in mind as an etiological factor of upper GI perforation especially in old age patients. To the best of our knowledge no previous data on such an association has been reported in our country. Keywords: Gastric perforation; Laparotomy; Ulcer; NSAIDs; Malignancy; Fungal infection